Middle Cerebellar Peduncle Lesions and Their Relation to Affective and Cognitive Impairment in Multiple Sclerosis - Eman Hamdy; Ismail Ramadan; Jaidaa Mekky; Dina Gaber; Aya Abdel Gleel (International Clinical Neuroscience Journal, 2022)
Background: Cerebellum has long been known to modulate not only motor coordination but also affective and cognitive functions. This study aimed to assess the impact of middle cerebellar peduncle (MCP) lesions on affective and cognitive function in patients with multiple sclerosis (MS). Methods: This was a cross-sectional study conducted on patients with relapsing-remitting MS (RRMS). All patients were subjected to 3-Tesla magnetic resonance imaging (3T MRI), brief international cognitive assessment for MS (BICAMS), and Depression, Anxiety, and Stress Score-21 (DASS-21) upon recruitment. Results: Of the 30 patients recruited, 33.3% and 36.7% had right and left MCP lesions, respectively. Patients with right MCP lesions had significantly worse symbol digit modality test (SDMT) scores (P=0.036), worse California verbal learning test (CVLT) immediate recall scores (P=0.011), and worse CVLT delayed free recall scores (P=0.049), whereas patients with left MCP lesions had lower DASS-21 scores (P<0.005). On multivariate regression analysis, the presence of left MCP lesion was associated with an 8.9-point reduction in DASS-21 scores (CI: -16.985- -0.805, P=0.033), whereas right MCP lesions did not have an independent effect on BICAMS scores after adjustment for age and educational level. Conclusion: Left MCP lesions were associated with significantly lower DASS-21 scores, whereas none of the MCP lesions had an independent impact on cognition.